2013
DOI: 10.3329/seajph.v2i1.15268
|View full text |Cite
|
Sign up to set email alerts
|

Study on reasons of dropout of EPI vaccination in selected slum area of Dhaka city, Bangladesh

Abstract: This cross sectional study carried out at a selected slum in Dhaka city, Bangladesh. The objective of the study was to examine the reasons of dropout of EPI vaccination among the children of slum areas. Mothers having children 11-23 months with history of EPI dropout were included in the study. A total of 128 mothers were interviewed. Out of 128 respondents 32.8% were in the age of 26-30 yrs; 96.9% were married, 65.7% were housewife, 62.5% had 4-6 members in the family, 50.78% had primary education & rest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…It was noticed that caretakers do not vaccinate their children as they forget or were not aware of the next dose or session site, feared any side effects, unsuitable session timing, an inappropriate attitude of the health staff, loss of daily earnings and no incentives or motivations for vaccinating. These observations are similar to those documented by other studies [9, 24–27].…”
Section: Discussionsupporting
confidence: 93%
“…It was noticed that caretakers do not vaccinate their children as they forget or were not aware of the next dose or session site, feared any side effects, unsuitable session timing, an inappropriate attitude of the health staff, loss of daily earnings and no incentives or motivations for vaccinating. These observations are similar to those documented by other studies [9, 24–27].…”
Section: Discussionsupporting
confidence: 93%
“…This is supported by a study done in Bangladesh. In this study, dropout rates were heightened by inadequate information about the immunization schedule [17]. In an effort to improve adherence to the immunization schedule, one of the strategies focusing on health systems is providing adequate information to caregivers either as groups or one on one, as indicated by this study.…”
Section: Achievable Strategies Focusing On the Health System Thatmentioning
confidence: 88%
“…This can lead to serious implications in terms of misconception or not understanding the importance of vaccines, etc. Poor counselling and limited information with respect to benefits or adverse effects of immunization, scheduling, number of sessions, age at which immunization is started are some of the reasons that contribute to the problem of incomplete immunization (Tagbo et al, 2014; Rahman et al, 2012; Maina et al, 2013; Zewdie et al, 2016). In several qualitative studies it has been shown that mothers who are afraid of vaccine adverse effects, either decline or delay subsequent immunizations (Smith et al, 2017).…”
Section: Discussionmentioning
confidence: 99%